Spring Boot essentials. (Manning Publications, 2022)
How would you like to work with the most important technology to hit Java enterprise development since the Spring Framework itself? That technology is Spring Boot, a Java-based open-source framework that makes it faster and easier for you to develop standalone applications and microservices that run on the JVM (Java Virtual Machine). And the first step to learning Spring Boot is understanding how, exactly, it works, and what, exactly, goes on inside a Spring Boot application. That understanding is exactly what you'll gain from this course. In this video series, we take you on a deep tour of sample Spring Boot apps, so you can see the inner workings, of the controllers and web layer, the repositories and data layer, starter dependencies, and much more. This course will empower you by unlocking the mechanics of Spring Boot so you know what's going on inside a Spring Boot program. With this excellent foundation, you will feel at ease exploring further and tapping into the versatile and powerful platform of Spring Boot.